Cost-effective flow injection spectrophotometric assay of iron content in pharmaceutical preparations using salicylate reagent - Udnan Y. (2014)
A new flow injection procedure for an assay of Fe(III) by using salicylate obtained from antipyretic powder, which is a cheap and easily available reagent, is proposed. A red complex was continuously monitored by a laboratory-made green LED colorimeter. A linear calibration was obtained in the range of 1-20 mg Fe l-1 with a detection limit of 0.5 mg Fe l-1 and R.S.D.s of 1.4-5.4% (n=3, for 1-20 mg Fe l-1). The new procedure was applied to assay iron contents in pharmaceutical preparations. The results were in good agreement with those of the USP standard method. © 2004 Published by Elsevier B.V.